Phylospecies in the Mexican marine algal diversity and the problem of morphospecies - María Luisa Núñez Resendiz; Kurt M. Dreckmann; Abel Sentíes; Martha I. Vilchis; Oscar E. Hernández; Sinuhé Hernández-Márquez; María Eugenia Zamudio-Resendiz (Botan‪ical Sciences)
Algae constitute a non-natural group of organisms that share morphological, physiological and ecological characteristics due to a complex shared evolutionary history. They live attached to a substrate or floating in a column of fresh or marine water. These latter are classified into macro and microalgae, whose current diversity recorded in Mexico is represented by approximately 1,700 species of macroalgae and 1,500 of microalgae. However, this diversity is based on morphological attributes. The problem of the morphospecies is that it depends on the expression of the genotype in response to the environmental heterogeneity in which these organisms establish themselves, resulting in phenotypic plasticity or morphological monotony, with the consequent overlapping of characters, generating misidentifications with several taxonomical problems associated and unstable classification systems. The molecular characterization of species has generated great taxonomic changes and more robust classifications. Currently, the diversity of Mexican phylospecies is reduced, with only 250 macro and microalgae, representing 12.5 and 2.3 % of the diversity, respectively. However, of the 142 works associated with phylospecies, 82 have led to taxonomic changes and proposals with important implications in the construction of more stable classification systems and a better understanding of Mexican phycofloristic diversity in all groups.